Phase tuning system for travelling wave resonator - Bondarenko, T.V.; Shchedrin, I.S. (Вопросы атомной науки и техники, 2013)
The article describes the system of phase tuning based on waveguide phase shifter. Phase shifter is represented by the dielectric plate with low dielectric permittivity placed inside a travelling wave resonator waveguide ring close to the narrow wall. Phase shift is defined by the plate displacement relative to the waveguide wall. Plate displacement is introduced by the stepping motor providing high precision of the positioning or manually. Graphs of electrodynamic characteristics dependences from the plate position and its parameters are listed. Several variants of motion input into the vacuum volume are described.